USE OF TECHNOLOGY IN TEACHING READING SKILLS (Journal of Universal Science Research, 2024)
The integration of technology into education has revolutionized traditional teaching methodologies, particularly in the realm of reading instruction. This article investigates the efficacy of various technological tools and strategies in enhancing reading skills among students. Utilizing a mixed-methods approach, the study encompasses a comprehensive literature review, surveys, interviews, and a controlled experimental study to evaluate the impact of technology on reading proficiency, engagement, and comprehension. Findings reveal that technology not only improves reading proficiency and engagement but also offers personalized and accessible learning experiences. Despite these benefits, challenges such as the need for educator training and ensuring equitable access to technology persist. The article concludes that while technology holds significant promise for improving reading skills, addressing these challenges is crucial for maximizing its potential in educational settings.